Modeling of tsunami propagation in the vicinity of the southern coasts of Iran - Heidarzadeh, Mohammad; Pirooz, Moharram D.; Mokhtari, Mohammad; Zaker, Nasser H. (Volume 5: Ocean Space Utilization; Polar and Arctic Sciences and Technology; The Robert Dean Symposium on Coastal and Ocean Engineering; Special Symposium on Offshore Renewable Energy, 2007)
The extensive death toll and sever economical damages brought by the 2004 Indian Ocean tsunami has emphasized the urgent need for assessing the hazard of tsunami in this ocean, and determining the most vulnerable coastlines to the impact of possible tsunami. In this paper the hazard of tsunami for southern coasts of Iran bordering the Indian Ocean is discussed. At first, historical data of tsunami occurrences on the Iranian southern coasts are collected, described and analyzed. Then, numerical simulation of potential tsunamis in the Makran subduction zone is performed and the tsunami wave height distribution along the Iranian coast is calculated. The Makran subduction zone is among two main tsunamigenic zones in the Indian Ocean. In this zone the Oman oceanic plate subducts beneath the Iranian Micro-plate at an estimated rate of about 19 mm/yr. Historically, there is the potential for tsunami generation in this region and several tsunamis attacked the Makran coastlines in the past. The most recent tsunami in this region has occurred on 28 November 1945 which took the lives of more than 4000 people in the coasts of Iran, Pakistan, India, and Oman. Here we examine the seafloor uplift of the Makran zone and its potential for generating destructive tsunamis in the southern coastlines of Iran. Several earthquake scenarios with moment magnitudes ranging between 6.5 and 8.5 are used as initial conditions for analysis. For scenario of an earthquake with magnitude of 8.0, propagation of tsunami waves on coastlines and wave time histories in selected reference locations are calculated.